STRATEGI PENINGKATAN JUMLAH PASIEN DI RSUD SUMBERSARI BANTUL MELALUI OPTIMALISASI PELAYANAN DAN PROMOSI KESEHATAN - Aprilianingsih, Maya; Mayasari, Fitri; Mayasari, Nada Cahya Pramesti; Aprilianingsih, Tsabita Hanan Faiza; Diky Saputra; Sevita Sari; Finda Novita Anggreeni (Journal of Hospital Administration and Excellent Health Service, 2025)
Sumbersari Bantul Regional Hospital, as a type D public hospital, faces challenges in increasing patient visits, especially amidst the growing competition among healthcare facilities. This study aims to analyze the hospital's strategies to increase outpatient and inpatient visits. The research employed a descriptive qualitative approach through observation and interviews with key units such as public relations, medical services, and medical records. The results indicate that the main strategies include improving service quality, utilizing social media for promotion, collaborating with primary healthcare centers (PHCs), and enhancing the role of customer service. The discussion highlights that optimizing services and external communication strategies are crucial in increasing patient satisfaction and loyalty. This study recommends strengthening quality management, digitizing promotions, and conducting routine patient satisfaction evaluations.